STRATEGI DAKWAH USTADZ ABI AZKAKIA MELALUI PLATFORM ROBLOX DI ERA DIGITAL - Muhamad Iqbal; Dzulfikar Adirais; Ahmad Sarbini; Asep Iwan Setiawan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This research examines the paradigm shift of da’wah (Islamic propagation) into immersive cultural platforms like Roblox, the digital habitat for Generations Z and Alpha. This phenomenon is termed da’wah gamification, requiring strategic adaptation to disseminate religious messages effectively. The main objective is to analyze the architecture of Ustad Abi Azkakia’s da’wah strategy on the Roblox metaverse platform, utilizing the framework of Muhammad Abu Al-Fatah Al-Bayanuni’s Da’wah Strategy Theory. The study employs a qualitative approach with an instrumental case study design, leveraging virtual ethnography and digital document analysis. The findings indicate that the da’wah strategy is fundamentally dominated by the Al-Manhaj Al-Hissi (Sensory Approach), transforming the verbal sermon into an active, lived experience for the audience (ritual simulations/virtual communal assemblies). The Al-Manhaj Al-Athifi (Sentimental Approach) serves to build communal affection. However, the Al-Manhaj Al-Aqli (Rational Approach) is significantly reduced and reconfigured into quick, lightweight content to suit the platform’s